Anatomical characteristics of the wood of six Pinus (Pinaceae) species of the state of Durango, México - de la Paz-Pérez Olvera, Carmen; Dávalos-Sotelo, Raymundo (Instituto de Ecología, A.C., 2016)
The anatomical characteristics of the wood of Pinus arizonica Engelmann, P. cooperi C. E. Blanco, P. durangensis Martínez, P. herrerae Martínez, P. leiophylla Schlecht. & Cham. and P. teocote Schlecht. & Cham are presented. The study material was obtained from two to four trees per species collected in pine-oak forests in the municipalities of Santiago Papasquiaro, San Dimas and Durango, in the state of Durango, Mexico. To observe the microscopic characteristics, slices of 20 µm in thickness were cut and stained with rapid green-safranin or with astra blue-basic fuchsine and dissociated material stained with Bismarck brown. For the macroscopic characteristics, specimens of 7 cm × 5 cm × 1 cm were produced. The proportion of early-wood is three times greater than that of late-wood in all of the specimens; the values of wall thickness and lumen diameter differed between early and late wood. Radii and axial resin canals presented differences in size and abundance. Pinus herrerae presents the widest rings and P. leiophylla and P. teocote the narrowest. The macroscopic characteristics of the six species studied are generally similar among individuals of the same species, regardless of collection site. Wood color and grain are influenced by the proportions of early and late woods present in each ring and the width of those characteristics. Pinus arizonica and P. cooperi presented differences in color between the sapwood and heartwood. The results are presented in tables and illustrated with photographs.